A Multiyear Survey and Identification of Pepper- and Tomato-Infecting Viruses in Yunnan Province, China - Li, Yueyue; Tan, Guanlin; Xiao, Long; Zhou, Wenpeng; Lan, Pingxiu; Chen, Xiaojiao; Liu, Yong; Li, Ruhui; Li, Fan (Frontiers in Microbiology, 2021)
During pepper and tomato production seasons in 2013 to 2017, we conducted a large-scale surveys in different regions of the Yunnan Province, China. A total of 1,267 pepper and tomato samples with various virus-like symptoms were collected and analyzed for virus infections through dot-enzyme-linked immunosorbent assay (Dot-ELISA), polymerase chain reaction (PCR), and reverse-transcription (RT)-PCR. The detection results showed that nineteen different viruses were present in about 50.9% of the assayed samples, and among these viruses, seven viruses were found in both pepper and tomato samples. Mixed infections with two to three of the 15 identified mixed infection types were found in the pepper samples and 10 identified mixed infection types were found in the tomato samples. Among the infected samples, Tomato spotted wilt orthotospovirus (TSWV) was the most commen virus, with a detection rate of about 20.0% followed by Pepper vein yellows virus (PeVYV, 13.0%). This survey revealed for the first time that pepper is a natural host of Tobacco vein distorting virus (TVDV) worldwide and tomato is a natural host of Potato leafroll virus (PLRV) in China. PeVYV, Tobacco mild green mosaic virus (TMGMV) and Wild tomato mosaic virus (WTMV) were not reported for pepper, and Tomato mottle mosaic virus (ToMMV) and Chilli veinal mottle virus (ChiVMV) for tomato in the Yunnan Province previously. Finally, the virus incidences were higher in the Kunming, Yuxi, Chuxiong, and Honghe region than other regions.